The Effect Of The Implementation Of Government Accounting Standards (Sap) Pp No. 71 Of 2010 On Financial Performance At The Bpkpd Of Binjai City - Asri Septiani; Nancy Mayriski Siregar; Miftha Rizkina (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of implementing Government Accounting Standards (SAP) based on Government Regulation No. 71 of 2010 on the financial performance of the Regional Financial and Revenue Management Agency (BPKPD) of Binjai City. The implementation of accrual-based SAP is an effort by the government to improve accountability, transparency, and the quality of regional financial reporting. This study uses a quantitative approach with a survey method. The research data was obtained by distributing questionnaires to 57 employees of the BPKPD of Binjai City who were directly involved in regional financial management and reporting. The data analysis techniques used included data quality testing, classical assumption testing, simple linear regression analysis, t-test, and coefficient of determination with the help of the SPSS program. The results show that the implementation of Government Accounting Standards (SAP) PP No. 71 of 2010 has not had a significant effect on the financial performance of Binjai City BPKPD. Nevertheless, the implementation of SAP still has a positive relationship and serves as a guideline in preparing financial reports that are more orderly, systematic, and in accordance with the provisions of laws and regulations. This study is expected to provide practical contributions to local governments in their efforts to improve financial management and serve as a reference for further research in the field of public sector accounting.